2023
DOI: 10.1101/2023.03.14.532599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population-level annotation of lncRNA transcription in Arabidopsis reveals extensive variation associated with transposable element-like silencing

Abstract: Background Long non-coding RNAs (lncRNAs) are under-studied and under-annotated in plants. In mammals, lncRNA loci are nearly as ubiquitous as protein-coding genes, and their expression has been shown to be highly variable between individuals of the same species. Using A. thaliana as a model, we aimed to understand the true scope of lncRNA transcription across plants from different regions and study its natural expression variability. Results Using RNA-seq data spanning hundreds of natural lines and several de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 104 publications
1
10
0
Order By: Relevance
“…Analyzing expression data from multiple accessions (Kawakatsu et al, 2016; Kornienko et al, 2023) generated from soil-grown plants without genotoxic stress indicated absence of transcripts of all three lncRNAs in the reference accession Col-0 seedlings (Supplemental Figure 5 A) but expression in seedlings from some other accessions under the same conditions. This is rare for lncRNA B but most common for lncRNA C (Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing expression data from multiple accessions (Kawakatsu et al, 2016; Kornienko et al, 2023) generated from soil-grown plants without genotoxic stress indicated absence of transcripts of all three lncRNAs in the reference accession Col-0 seedlings (Supplemental Figure 5 A) but expression in seedlings from some other accessions under the same conditions. This is rare for lncRNA B but most common for lncRNA C (Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%
“…To find the gene copies, the blastn results were filtered for sequences with >80% sequence identity and >80% length match to the TAIR sequence, allowing for insertions of up to 1.5 kb to account for possible TE insertions in the non-reference accession genomes. For gene expression calculation, we used RNA-seq data from mature leaves (Kawakatsu et al, 2016, GEO accession number GSE80744) and RNA-seq data from 7-day-old seedlings, 9-leaf rosettes, flowers (with flower buds), and pollen (Kornienko et al, 2023, GEO accession number GSE226691). Raw RNA-seq reads were mapped to the TAIR10 genome using STAR (v.2.7.1) and exonic read counts were calculated using feature counts software from the subread package (v.2.0.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A and EV1A). To determine their abundance in the genome, we defined four classes of TEs based on the length coverage of H3K27me3 marks and CG methylation, using these datasets and previously published methylomes 37 (Fig. 1B and EV1B).…”
Section: Many Tes Are Marked Solely By H3k27me3 In Wild-type Arabidop...mentioning
confidence: 99%
“…H3K27me3 and H2AZ (GSE103361) 40 , ref6 elf6 jmj13 H3K27me3 ChIP-seq (GSE106942) 43 and Ecotypes related data (GSE224761) 37 .…”
Section: Analyzed Data Setsmentioning
confidence: 99%